Case Report about Fatal or Near-Fatal Hypersensitivity Reactions to Cetuximab: Anticetuximab IgE as a Valuable Screening Test. (January 2014) - Dupont, Benoît; Mariotte, Delphine; Moldovan, Cristian; Grellard, Jean-Michel; Vergnaud, Marie-Claude; Laroche, Dominique; Gervais, Radj
Hypersensitivity reactions are a classic side effect of cetuximab. We report the cases of three patients who developed life-threatening hypersensitivity to cetuximab, which could have been predicted by assessing the concentration of serum anticetuximab immunoglobulin (Ig)E. The anti-cetuximab IgE concentration could be an interesting test to predict which patients are at risk of experiencing severe hypersensitivity reactions to cetuximab.